An examination of the efficacy and background of the Covid-19 vaccine: comparative analysis - Mahmoud, Al-Masaeed; M., Alghawanmeh; A., Al-Singlawi; R., Alsababha; M., Alqudah; A., Alomari; M., Alshawawreh; Rasdi, Irniza (Medwin, 2021)
Significance and Aim: The aim of this review is to instigate the existing literature on the efficacy levels of the administered Covid-19 pandemic vaccines. The review examines how the efficacy levels compare or contrast among the leading vaccines globally. The proposed value of the review is to indicate if the inoculation of the population has a significant value and impact on reducing exposure and risk of Covid-19 infection and severity of the disease. Methods: The review was developed as an ILR analysis. The search was made from 5 different databases. The findings were Scopus (103), Medline (78), Google Scholar (320), CINAHL (167), and WHO (201). By applying the review inclusion and exclusion criteria, the review settled on 21 articles included in the analysis. The findings were analysed thematically. Results and findings: The findings indicate that the vaccines analysed, the (i) Pfizer, (ii) Astra Zeneca, (iii) Johnson &, (iv) Moderna, can be categorised into two main levels, namely the mRNA vaccines and the carrier/ virus vector vaccines. The findings indicate that all the vaccines have a high efficacy index above the WHO threshold of 50% efficacy minimum. Pfizer has the highest efficacy based on the RCTs done at the manufacturing stage. Conclusion: In summary, the findings indicate the validity and value of vaccines in reducing the healthcare industry burden. The high efficacy levels on reducing the severity and hospitalisation needs allow for a reduced disease burden globally. Sensitisation is required for the global population base. Equally, more RCTs are required to test the efficacy of the existing vaccines against the emerging variants, such as the highly virulent delta variant.